Large non-functional adrenocortical oncocytoma with uncertain malignant potential: case report and review of literature - Yadav, Praveen Kumar; Hasan, Arshad; Singh, Anunay; Kundu, Gaurab; Haque, M. Faizul; Swain, Samir; Hota, Datteswar (International Surgery Journal, 2020)
Adrenocortical oncocytomas are a very rare group of adrenal tumors. Unless functional, these tumors are incidentally diagnosed for clinical manifestations that are unrelated to the adrenal gland. The majority of these oncocytomas are benign and nonfunctional. Very few cases of uncertain malignant potential are reported. Here we present such a rare case of a 60 years old man presenting with voiding lower urinary tract symptoms but on contrast enhanced computed tomography (CECT) abdomen and pelvis a fairly large well defined heterogeneously enhancing retroperitoneal mass lesion with calcifications in the left anterior pararenal space (measuring 10.8×9.7×9 cm) was detected. On excision a well encapsulated solid mass of size approximately 12×10×9 cm was present in left suprarenal region. Histopathological examination confirmed the diagnosis of adrenocortical oncocytoma with uncertain malignant potential. As the incidence of adrenal oncocytoma is less, the knowledge regarding its clinical pattern, confirmatory imaging or histopathological diagnostic tools and chances of recurrence or turning malignant is limited.